2021
DOI: 10.3390/metabo11010059
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity-Related Metabolites Are Associated with Mortality: Findings from the Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Habitual physical activity can diminish the risk of premature death. Identifying a pattern of metabolites related to physical activity may advance our understanding of disease etiology. We quantified 245 serum metabolites in 3802 participants from the Atherosclerosis Risk in Communities (ARIC) study using chromatography–mass spectrometry. We regressed self-reported moderate-to-vigorous intensity leisure-time physical activity (LTPA) against each metabolite, adjusting for traditional risk factors. A standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…A deficiency of human glycerate kinase leads to D-glycerate acidemia/D-glyceric aciduria. Our findings are consistent with a previous study that reported moderate-to-vigorous-intensity leisure-time PA is positively related to glycerate in both AAs and Whites in the respective and pooled samples [41]. Our findings suggest that PA may increase glycerate concentration, and the influence was dependent on regular PA frequency.…”
Section: Plos Onesupporting
confidence: 93%
“…A deficiency of human glycerate kinase leads to D-glycerate acidemia/D-glyceric aciduria. Our findings are consistent with a previous study that reported moderate-to-vigorous-intensity leisure-time PA is positively related to glycerate in both AAs and Whites in the respective and pooled samples [41]. Our findings suggest that PA may increase glycerate concentration, and the influence was dependent on regular PA frequency.…”
Section: Plos Onesupporting
confidence: 93%
“…Using a weighted correlation network analysis on 102 metabolites, 8 distinct sedentary metabolite modules on 56 highly connected metabolites were identified, excluding 46 metabolites with low overall connectivity (Fig. 2, the average of module size was 7 metabolites composing a module; range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. We named the modules, by the most frequently represented pathways in the module, as BCAA, erythritol, PUFA, creatine, urea cycle, plasmalogen glycerol phosphatidyl ethanolamine (GPE)-ethanolamine plasmalogen subclass, plasmalogen GPC, and acyl choline.…”
Section: Resultsmentioning
confidence: 99%
“…There are several epidemiological studies examining the metabolomic shifts by habitual physical activity (6)(7)(8)(9)(10)(11)(12), but only a few studies addressing sedentary time (8)(9)(10). Consistent with cellular and physiological mechanisms of physical activity (4), metabolomic profiling supports (13) that physical activity may activate the catabolism of branched-chain amino acids (BCAA) linked with increased mitochondrial fatty acid oxidation (low BCAA and its derivative 4-methyl-2-oxopentanoate) (6,8,9), glucose homeostasis (low glucose, alanine, proline, and lactate) (6,(8)(9)(10), and anti-inflammatory pathway (low glycoprotein acetyls) (10).…”
mentioning
confidence: 99%